2003
DOI: 10.1016/s0014-5793(03)00383-1
|View full text |Cite
|
Sign up to set email alerts
|

Critical regions for the sweetness of brazzein1

Abstract: Brazzein is a small, heat-stable, intensely sweet protein consisting of 54 amino acid residues. Based on the wild-type brazzein, 25 brazzein mutants have been produced to identify critical regions important for sweetness. To assess their sweetness, psychophysical experiments were carried out with 14 human subjects. First, the results suggest that residues 29^33 and 39^43, plus residue 36 between these stretches, as well as the C-terminus are involved in the sweetness of brazzein. Second, charge plays an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 13 publications
1
65
0
1
Order By: Relevance
“…The present work studied the hydrophobicity through carbon content on a number of brazzein mutants previously reported with focus on the two critical regions of the molecule suggested to be responsible for its sweetness [1,8,9,15]. As revealed in the results, the two regions with residues 29-33 and 39-43 including residue 36 between these segments, exists a remarkable variation between brazzein mutants with the increased sweetness taste mainly at residues 29, 31 and 41 and mutants with reduced sweetness taste at residues 30, 33, 36 and 43.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present work studied the hydrophobicity through carbon content on a number of brazzein mutants previously reported with focus on the two critical regions of the molecule suggested to be responsible for its sweetness [1,8,9,15]. As revealed in the results, the two regions with residues 29-33 and 39-43 including residue 36 between these segments, exists a remarkable variation between brazzein mutants with the increased sweetness taste mainly at residues 29, 31 and 41 and mutants with reduced sweetness taste at residues 30, 33, 36 and 43.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies using different approaches have reported that charge was important for producing sweetness in brazzein and indicated that mutating positive charges to neutral or negative charge significantly decreases the sweetness in brazzein [1]. Other studies have also reported that mutations decreasing the overall negative charge and/or increasing the positive charge favors sweet-tasting protein strength [11,26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations